Hyperscanning: Simultaneous fMRI during Linked Social Interactions - Montague, P.Read; Berns, Gregory S.; Cohen, Jonathan D.; McClure, Samuel M.; Pagnoni, Giuseppe; Dhamala, Mukesh; Wiest, Michael C.; Karpov, Igor; King, Richard D.; Apple, Nathan; Fisher, Ronald E. (NeuroImage (Orlando, Fla.), 2002)
“Plain question and plain answer make the shortest road out of most perplexities.” Mark Twain- Life on the Mississippi A new methodology for the measurement of the neural substrates of human social interaction is described. This technology, termed “Hyperscan,” embodies both the hardware and the software necessary to link magnetic resonance scanners through the internet. Hyperscanning allows for the performance of human behavioral experiments in which participants can interact with each other while functional MRI is acquired in synchrony with the behavioral interactions. Data are presented from a simple game of deception between pairs of subjects. Because people may interact both asymmetrically and asynchronously, both the design and the analysis must accommodate this added complexity. Several potential approaches are described.